Generation and engineering of potent single domain antibody-based bispecific IL-18 mimetics resistant to IL-18BP decoy receptor inhibition - Britta Lipinski; Laura Unmuth; Paul Arras; Stefan Becker; Christina Bauer; Lars Toleikis; Simon Krah; Achim Doerner; Desislava Yanakieva; Ammelie Svea Boje; Katja Klausz; Matthias Peipp; et al. (mAbs, 2023)
Here, we generated bispecific antibody (bsAb) derivatives that mimic the function of interleukin (IL)-18 based on single domain antibodies (sdAbs) specific to IL-18 Rα and IL-18 Rβ. For this, camelids were immunized, followed by yeast surface display (YSD)-enabled discovery of VHHs targeting the individual receptor subunits. Upon reformatting into a strictly monovalent (1 + 1) bispecific sdAb architecture, several bsAbs triggered dose-dependent IL-18 R downstream signaling on IL-18 reporter cells, as well as IFN-γ release by peripheral blood mononuclear cells in the presence of low-dose IL-12. However, compared with IL-18, potencies and efficacies were considerably attenuated. By engineering paratope valencies and the spatial orientation of individual paratopes within the overall design architecture, we were able to generate IL-18 mimetics displaying significantly augmented functionalities, resulting in bispecific cytokine mimetics that were more potent than IL-18 in triggering proinflammatory cytokine release. Furthermore, generated IL-18 mimetics were unaffected from inhibition by IL-18 binding protein decoy receptor. Essentially, we demonstrate that this strategy enables the generation of IL-18 mimetics with tailor-made cytokine functionalities.